Eskimo languages in Asia, 1791 on, and the Wrangel Island-Point Hope connection - Krauss, Michael (Études/Inuit/Studies, 2005)
AbstractMerck’s statement about four “Sedentary Chukchi” (Eskimo) languages or language varieties along the coast of Chukotka in 1791 is thoroughly remarkable and worthy of careful interpretation. By his statement of their geographical distribution, the first three languages are very easy to identify, as 1) Sirenikski, 2) Central Siberian Yupik, explicitly including St. Lawrence Island, and 3) Naukanski. Merck’s language number four, “Uwelenski” he claims, startlingly, to be spoken along the Arctic Coast of Chukotka from Uelen as far as Shelagski Cape, 600 miles to the northwest. Serendipitously enough, Merck has 70 or so ”Uwelenski” words of cultural interest transcribed throughout his text. Careful studies of these words by this writer and also by Mikhail Chlenov show that “Uwelenski” is in fact a dialect of Central Siberian Yupik, thus part of a language continuum spoken from St. Lawrence Island to the Chaplino corner and the East coast of Chukotka, thence to the North coast of that mainland, treating Naukan as a “third Diomede” rather than as a mainland interruption. However there is no evidence that language number four, “Uwelenski,” actually a dialect of Merck’s language number two, was spoken beyond Kolyuchin Bay. Beyond that point, however, there was indeed a fourth Eskimo language. The second half of the paper concludes, from at least seven independent sources, that that fourth language was in fact none other than North Alaskan Inupiaq, spoken intermittently in pockets between Kolyuchin and Shelagski Cape, at least since the opening of Russian posts at Kolyma and into the nineteenth century, by north Alaskans from the Point Hope area, who also used Wrangel Island as a stopping place.